The Cobres Plutonic Complex, eastern Puna (NW Argentina): Petrological and structural constraints for Lower Paleozoic magmatism - Kirschbaum, Alicia Matilde (2006)
The southern portion of the Cobres Range is studied with an interdisciplinary, petrological–geochemical and structural-cartographic approach. The Cobres Plutonic Complex (CPC) consists of two main plutons, a granodiorite and a monzogranite, as well as small bodies of gabbros, acidic dikes, and episyenite bands. Their mineralogy and geochemistry suggest a comagmatic character for both plutons, which are strongly peraluminous and define a typical calc–alkaline trend. Harker diagrams indicate a fractionated crystallization trend. The REEs have similar patterns for enclaves, granodiorites, monzogranites, aplites, and acidic dikes, also similar to those from the upper crust rocks. Gabbros included in the CPC show geochemical signatures compatible with the mantle. The CPC is syntectonic, though the granodioritic and monzogranitic plutons represent different stages in the tectomagmatic history of the region. The geology of the CPC and its regional framework show characteristics—thermal anomalies, alternation of contractional and extensional deformational events, magmatic rocks with crustal and mantle affiliations, and contemporaneous extensional basins—that indicate intrusion of the CPC in an extensional accretionary orogen.